Nanotechnology in Dentistry - Arruda, José Alcides Almeida de; Oliveira, Cinthia Figueiredo de; Paula, Carina Silva de; Mosqueira, Vanessa Carla Furtado; Moreno, Amália; Mesquita, Ricardo Alves (ARCHIVES OF HEALTH INVESTIGATION, 2017)
Introduction: Nanotechnology is a rapidly expanding field that encompasses the development, manipulation, and application of structures on the nanometer scale. Applications of nanotechnology to dentistry are particularly promising and comprise materials and devices designed to achieve maximal therapeutic efficacy with minimal side effects. Objective: This review discusses the advantages of nanotechnology and the different types of nanostructures used in dentistry. Material and Method: In this study, online databases: pubmed, medline and scielo were searched to analyse the current understanding of the potential of nanotechnology in dentistry, including the restoration of tooth structure with nanocomposites and the development of nanoparticles for dentin remineralisation, drug delivery, disease diagnostics, oral analgesia, oral hygiene maintenance, local anaesthesia, tooth desensitisation, and bone tissue repair. Results: The study demonstrated a wide range of nanotechnological strategies in different dentistry areas and suggests that nanotechnology-based delivery systems may be very useful to improve treatment, prevention and repair in dentistry in the future. Conclusion: There is little or no clinical experience for the nanotechnology-based drug delivery systems cited herein. Safety assessments and clinical trials are the next step in their development. Descriptors: Nanotechnology; Dental Research; Biocompatible Materials.